(untitled) (Research, Society and Development, 2021)
In recent years, the aging of the population has been considered something of great concern for public health, since with the aging of the population, chronic non- communicable diseases have occupied a prominent place in the context of public health in Brazil. Arterial hypertension has become a more frequent disease in recent years, affecting mainly elderly patients. Even with actions and projects to reduce the risks of the incidence of hypertension, several factors may be associated with the onset of the disease, requiring monitoring by a qualified professional. The problem with this work is: What are the possible problems related to medication use by hypertensive patients? The general objective of this work is to address the importance of pharmaceutical care for hypertensive patients. The methodology used in this work was a bibliographic research gathered through monographic research, articles, magazines, periodicals and books related to the theme. As a result of this work, it can be stated that the pharmacist is an extremely important professional for the pharmacotherapeutic follow-up of a hypertensive patient, since he is also the closest professional to users in pharmacies and drugstores. The pharmacist’s follow- up enables improvement in treatment and continuity with the rational use of the medication.